Filiation symbolique : le refus de la puissance paternelle dans Œdipe roi de Pier Paolo Pasolini - Frach, Sylwia (Romanica Silesiana)
The parent–child relationship is omnipresent in the works of Pier Paolo Pasolini. In Oedipus Rex, the filmmaker uses both the original myth and Sophocles’ tragedy to underline the fact that the father–son relationship is rooted in the Ancient World. Moreover, as will be depicted later on, Pasolini uses the work to evoke his personal experiences and artistic style. In this sense, the film is founded on psychoanalytic theories. Oedipus embodies the heart of Freudian thought: metahistorical hatred against the father, patricide and incest on the one hand, nostalgia and longing for the mother’s womb on the other. At the epicenter of this reflection lies the Oedipal theme of father–son relationship coupled with his digressions.